Thermal insulation packaging for cold-chain deliveries made from feathers. (September 2019) - Dieckmann, Elena; Nagy, Balázs; Yiakoumetti, Kika; Sheldrick, Leila; Cheeseman, Christopher
Highlights: Feather fibres have been processed to form air laid non-woven mats. These have low thermal conductivity and can form thermally insulating packaging. There is an increasing market for insulated packaging boxes for food delivery. Feather fibre mats give similar cool box performance to expanded polystyrene. Feather fibre mats can displace materials currently used for chilled delivery. Abstract: This paper reports on new thermal insulation packaging materials made from feathers. Clean and disinfected feathers from the poultry industry have been processed into fibres and air laid using commercial pilot-plant facilities to form non-woven feather fibre composite mats. This process can produce materials with different thickness and density by varying the processing conditions and mat composition. The thermal performance of non-woven feather fibre packaging liners has been compared to expanded polystyrene (EPS) to assess the potential for use in temperature-controlled deliveries. Experiments involved monitoring the time-temperature profile of meat substitute materials and coolants stored inside cardboard boxes lined with thermal insulation. The results show that feather fibre composite insulation has comparable thermal performance to EPS and may out-perform EPS under some conditions. It is concluded that low-cost, lightweight and sustainable non-woven feather fibre liners have potential to displace the materials currently used for delivering chilled and frozen foods and other products susceptible to degradation by high temperatures during delivery.